Conceptualizing the Implementation of Deep Learning in ELT through Cooperative Learning for Teaching Speaking Skills at the High School Level - Safira, Salsa; Astuti, Puji (Universitas Negeri Semarang, 2025)
This conceptual article explores the integration of Deep Learning principles into English Language Teaching (ELT) through the Cooperative Learning technique, Number Head Together (NHT), to enhance students’ speaking skills in Indonesian high school classrooms. This instructional model is constructed within the Genre-Based Approach (GBA) framework and aims to support the implementation of the Emancipated Curriculum. By aligning with the principles of mindful, meaningful, and joyful learning, this model encourages students to think critically, engage in collaborative discussions, and apply language in real-life contexts. This article provides a detailed explanation of how Cooperative Learning techniques can be strategically used to manifest Deep Learning, particularly in teaching high school students to express opinions. Through theoretical exploration and a structured instructional strategy, this framework offers practical implications for English teachers to design effective, student-centered speaking lessons that foster both language proficiency and higher-order thinking skills.